Tuning SpyTag–SpyCatcher mutant pairs toward orthogonal reactivity encryption - Liu, Yajie (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Genetically encoded covalent peptide tagging technology, such as the SpyTag–SpyCatcher reaction, has emerged as a unique way to do chemistry with proteins. Herein, we report the reactivity engineering of SpyTag–SpyCatcher mutant pairs and show that distinct reactivity can be encrypted for the same reaction based on protein sequences of high similarity. Valuable features, including high selectivity, inverse temperature dependence and (nearly) orthogonal reactivity, could be achieved based on as few as three mutations. This demonstrates the robustness of the SpyTag–SpyCatcher reaction and the plasticity of its sequence specificity, pointing to a family of engineered protein chemistry tools.